Impact of Stock Market Volatility on Bank Performance in Nepal: A Case of Nepalese Commercial Banks - Khadka, Prem; Chaudhary, Prashant; Nepal, Prasnil; Thakur, Niyasha Kumari; Rawat, Ramesh (Nepalese Journal of Economics, 2024)
This study examines the impact of stock market volatility on the performance of Nepalese commercial banks. Return on equity and return on assets are selected as the dependent variables. The selected independent variables are dividend per share, earnings per share, loan to deposit ratio, leverage, market price per share, and P/E ratio. The study is based on secondary data with 105 observations for the period of 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of respective commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of stock market volatility on the performance of Nepalese commercial banks. The study showed that market price per share has a positive impact on return on equity and return on assets. It indicates that increase in market price per share leads to increase in return on equity and return on assets. Similarly, loan to deposit ratio has a negative impact on return on equity and return on assets. It indicates that increase in loan to deposit ratio leads to decrease in return on equity and return on assets. Likewise, earnings per share have a positive impact on return on equity and return on assets. It indicates that increase in earnings per share leads to increase in return on equity and return on assets. Further, dividend per share has a positive impact on return on equity and return on assets. It indicates that increase in dividend per share leads to increase in return on equity and return on assets. In addition, leverage has a negative impact on return on equity and return on assets. It indicates that increase in leverage leads to decrease in return on equity and return on assets. Likewise, P/E ratio has a positive impact on return on equity and return on assets. It indicates that increase in P/E ratio leads to increase in return on equity and return on assets.